2004
DOI: 10.1111/j.1365-2559.2004.01976.x
|View full text |Cite
|
Sign up to set email alerts
|

Tenascin‐C in primary malignant melanoma of the skin

Abstract: In primary melanoma of the skin, absence of Tn-C in the stroma of invasion fronts and within tumour cells seems to be related to a more benign disease behaviour with a lower risk of developing metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 35 publications
(45 reference statements)
0
19
0
Order By: Relevance
“…These proteins were either not identified or were identified at very low abundance in the the collagen and non-injected SOC controls. Increases in the abundance of TN-C have been documented in MGP melanomas, and it has been suggested that relatively low levels of TN-C expression may be associated with a lower risk for metastasis19. Like TN-C, fibronectin is another protein implicated in melanoma invasion.…”
Section: Resultsmentioning
confidence: 99%
“…These proteins were either not identified or were identified at very low abundance in the the collagen and non-injected SOC controls. Increases in the abundance of TN-C have been documented in MGP melanomas, and it has been suggested that relatively low levels of TN-C expression may be associated with a lower risk for metastasis19. Like TN-C, fibronectin is another protein implicated in melanoma invasion.…”
Section: Resultsmentioning
confidence: 99%
“…In many cancer forms, such as breast [14, 15], lung [16], brain [17], urological [18, 19], malignant melanoma [20], pheochromocytoma [21], cholangiocarcinoma [22] and adipocytic tumors [23], a high tenascin-C expression has been correlated with a poor patient survival [5, 6]. While this correlation applies to some cancers, there are also reports where tenascin-C expression correlates with a lower stage of disease and a better patient outcome [5, 6, 24, 25].…”
Section: Introductionmentioning
confidence: 99%
“…It is not expressed in most adult normal tissues but transiently reappears after injury and regulates cell behavior by modulating cell adhesion [22]. It is linked to diverse reactive conditions such as inflammation and wound healing [28] as well as pathologic states including vascular disease and metastasis [21]. The growth-promoting properties of tenascin are due to the epidermal growth factor-(EGF-)like repeats contained in the protein [41].…”
Section: Discussionmentioning
confidence: 99%